2012
DOI: 10.1371/journal.pone.0045399
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibition of c-MYC in Myeloid Cells Impairs Tumor-Associated Macrophage Maturation and Pro-Tumoral Activities

Abstract: Although tumor-associated macrophages (TAMs) are involved in tumor growth and metastasis, the mechanisms controlling their pro-tumoral activities remain largely unknown. The transcription factor c-MYC has been recently shown to regulate in vitro human macrophage polarization and be expressed in macrophages infiltrating human tumors. In this study, we exploited the predominant expression of LysM in myeloid cells to generate c-Mycfl/fl LysMcre/+ mice, which lack c-Myc in macrophages, to investigate the role of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…10,11 It was not clear whether induction of c-MYC in M2-polarized macrophages is a primary event in response to IL4/IL13 stimulation or secondary to STAT6 (signal transducer and activator of transcription 6) activation. To clarify, c-MYC expression in macrophages from wild-type and STAT6-deficient mice was compared.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 It was not clear whether induction of c-MYC in M2-polarized macrophages is a primary event in response to IL4/IL13 stimulation or secondary to STAT6 (signal transducer and activator of transcription 6) activation. To clarify, c-MYC expression in macrophages from wild-type and STAT6-deficient mice was compared.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, MYCN has also been recently revealed as the most highly upregulated gene in macrophages upon the treatment of immune suppressive soluble factors that are released from apoptotic cells [48]. Once more, it was shown that inhibition of MYC in macrophages attenuates the protumor function of TAM and suppresses tumor growth [49].…”
Section: Twist1 Myc and Immune Systemmentioning
confidence: 99%
“…In this regard, we recently described that inhibiting MYC only in the myeloid compartment in mice reduces melanoma and fibrosarcoma tumor growth. 4,5 TAMs are generally considered "alternatively activated", M2 or M2-like macrophages, a group which refers to all macrophage subtypes which are activated by stimuli different from T helper type 1 (Th1) inflammatory cytokines, showing a specific phenotype and exerting particular functional activities. 6 Among these, the anti-inflammatory properties of M2 macrophages are needed to avoid exacerbated inflammatory responses and inflammation-related pathologies.…”
Section: Inhibition Of Myc In Macrophages: Tumor Vs Inflammation-relamentioning
confidence: 99%
“…6 Interestingly, mice lacking MYC in myeloid cells show a normal immune system in steady-state conditions compared to control littermates. 4,5 However, in response to an inflammatory stimulus like aortic denudation, these animals are less able to clear and resolve inflammation, which persists for an extended period of time. 7 Although the role of MYC in fully differentiated immune cells has only recently began to be elucidated in detail, assuming that M2 macrophages and other antiinflammatory cells express MYC, 2,8,9 would an antitumor treatment targeting MYC facilitate subsequent inflammationrelated disorders?…”
Section: Inhibition Of Myc In Macrophages: Tumor Vs Inflammation-relamentioning
confidence: 99%